POLITICAL POWER OF A CANDIDATE FOR THE PRESIDENT OF THE GOVERNMENT OF REPUBLIC OF SRPSKA: Testing concepts of R. Dahl and J. K. Galbraith on example of program and composition proposal introduction - Grebenar, Bojan (Politeia, 2021)
Within this work, we tested possibility of practical application of concepts of political power defined in Robert Dahl’s and John Kenneth Galbraith’s work. These concepts were tested on the practical case of election of the head of government in the Republic of Srpska. More precisely, introduction of the program and cabinet proposal in the National Assembly of Republic of Srpska by Milorad Dodik, candidate for the president of the Government of Republic of Srpska in November 2006. This was done first through the short introduction and analysis of four aspects of political power – base, means, scope and amount of power, and Galbraith’s three types of political power: condign, compensatory, and conditioned power. Based on identified elements and types of power, we defined the crucial questions to be considered in the analysis of individual cases from the political practice. After that, we applied these questions and concepts on concrete case of Milorad Dodik’s address to the National Assembly with proposition of his government program and composition. Results of this work show that Dahl’s and Galbraith’s concepts of political power have explanatory use in the analysis of political practice and processes. However, based on conducted analysis it can be noticed that they are limited because they do not include all elements that can affect political power. It can be concluded that comprehensive analysis of political power is made more difficult by nature of political processes and by their parts that stay secret and beyond reach of research and general public.